New Aspects in Molecular and Cellular Mechanisms of Human Carcinogenesis - Bulgin, Dmitry (IntechOpen, 2016)
Written by an international team of experts in the field of human carcinogenesis, this book discusses recent advances in cancer research, which include the following topics: basic molecular and cellular mechanisms behind cancer growth, new approaches in cancer therapy, and cancer diagnostic. The book serves as a useful source of reference for cancer biologists, medical doctors, and clinical researchers in the fields of cancer diagnosis, prevention, and treatment.